Wokół metodologii nauk o sztuce - Hendrykowski, Marek (Przestrzenie Teorii, 2019)
This article deals with the basic issues related to the evolution and methodology of research on art. The author highlights the close relationship between theory and practice of artistic activity and underlines the cognitive advantages stemming from the interdisciplinary approach of formulating and solving research questions in the domain of reflections on art.